Improving Student’s Reading Comprehension on Narrative Text Through Annotating Strategy at the Eighth Grade of SMP Al-Washliyah Hamparan Perak - Nur Afifah Fatin; Juliana Juliana (Universitas Muhammadiyah Enrekang, 2024)
This study aims to improve the reading comprehension of the eighth-grade students at SMP Al-Washliyah Hamparan Perak by using Annotating Strategy. The research adopts a Classroom Action Research (CAR) design, which conducted in two cycles. Each cycle is consisted of planning, action, observation, and reflection. The study subjects included 33 students who exhibited challenges in comprehending narrative texts, particularly in identifying main ideas and supporting details. The data of this study were collected through observation sheets, interviews, documentation, and reading comprehension tests. The analysis involved both qualitative and quantitative methods, which focused on the observation of classroom activities and the evaluation of students' performance through pre-test and post-test assessments. The results indicated a significant improvement in students' reading comprehension, with a noticeable increase in their ability to grasp narrative text content followed by the implementation of Annotating Strategy. The study recommends the wider adoption of this strategy in teaching reading comprehension, as it actively engages students in the reading process, thereby enhancing their understanding and retention of information.